Soil Chemistry Character, the N, P, and K Uptake, and the Growth and Yield of Corn (Zea mays L.) Due to the Application of Ela Sago Palm Waste Compost and Liquid Organic Fertilizer in Ultisols - Elizabeth Kaya; Adelina Siregar; Diane Matulessy; Masita Hasan; Arsando Akollo (UNIVERSITY OF LAMPUNG, 2022)
Application of organic matter (compost Sago Ela palm waste and Liquid Organic fertilizers (LOF)) to the soil could have major benefits, such as to improve the soil physical condition (soil structure, water retention), and soil chemical properties (binding and providing nutrients, increasing CEC). The purpose of this study are (1) to improve the soil chemical properties of Ultisols, and (2) to increase plant uptake of N, P, and K, and the growth and yield of corn (Zea mays L.). The research was conducted in the field, namely in Telaga Kodok Village, Leihitu Sub District, and Central Maluku District. The experiment was designed in a factorial, and arranged in a randomized completed block design (RCBD). The first factor was the provision of compost Sago Ela palm waste (K) and the second factor was the provision of liquid fertilizer (C). The results showed that the compost combined with LOF could improve pH, Al-exchangeable, Total-N, P-available soil, Uptake-P, Uptake-K, and the dry weight of seed corn. While the treatment of sago Ela palm waste compost and LOF can independently raise the K-available soil, N-uptake, and affect corn’s plant growth (height and trunk diameter). The treatment doses of sago Ela palm waste compost of 60 Mg ha-1 and LOF of 20 mL L-1 solution can increase the exchangeable Al, Total-N, and P-available soil, respectively 0.56 cmol(+)kg-1, 0.21%, and 31.00 mg kg-1; also able to increase the uptake of P, K, and weight dry seed corn respectively 0.21% and 1.26%, and 121.33 g plant-1. The treatment doses of Sago Ela palm waste compost of 60 ton ha-1 and liquid organic fertilizer of 10 mL L-1 solution can increase the soil pH by 5.70.